The Effect of Tourism Sector on Locally-Generated Revenue Income in Banyumas District - Windanila Sri Kuswari; Abdul Aziz Ahmad; Diah Setyorini Gunawan (Universitas Batanghari, 2021)
This study aimed to analyze the effect of the number of foreign tourists, domestic tourists, the number of tourist attractions and the number of hotels on the Growth of locally-generated revenue in in the Barlingmascakeb region in 2010-2019. The research method used multiple linear regression with the panel data approach. The results showed that the number of foreign tourists and domestic tourists had a positive and significant effect on the Growth of locally-generated revenue in the Barlingmascakeb region. Meanwhile, the number of tourist attractions and the number of hotels have no effect on the Growth of locally-generated revenue in in the Barlingmascakeb region. The policy implication in the research is the need for the development of the tourism sector and its supporting infrastructure.